Neonatal complications and risk factors among women with gestational diabetes mellitus - Schneider, Sven; Höft, Birgit; Freerksen, Nele; Fischer, Burkhard; Röhrig, Silke; Yamamoto, Shelby; Maul, Holger (Acta obstetricia et gynecologica Scandinavica, 2011)
Objective. This study aimed to identify risk factors for gestational diabetes mellitus (GDM) and assess the effects of GDM on the risk of adverse pregnancy outcomes. Material and methods. This was a cross-sectional study using data from the German Perinatal Quality Registry, which is a complete national registry containing information on all hospital births across Germany. The Registry for 2006 contains data on a complete birth cohort of 668,085 newborn infants and 647,392 mothers from all 896 German hospitals. All data were taken from maternity log records and analyzed by multivariate logistic regression. Each recorded case of GDM was identified by a gynecologist or in hospital. Results. The prevalence of GDM was 2.3% (14,990 of 647,385). High-risk groups were migrants, women of lower socioeconomic status (adjusted odds ratio 1.16, 95% confidence interval 1.05-1.28) and obese women (adjusted odds ratio 4.96, 95% confidence interval 4.70-5.24). A higher risk of fetal malformations was found for those diagnosed with GDM (adjusted odds ratio 1.32, 95% confidence interval 1.15-1.53). Conclusion. The higher risk of fetal malformations with GDM suggests that many of these women may have high glucose levels even during the first trimester. Policies and interventions regarding prenatal care should therefore focus not only on how better diagnostic and treatment procedures can be implemented, but also on how they can reach older and migrant women as well as women of lower socioeconomic status.